RANCANG BANGUN MEDIA INTERAKTIF PADA MATA PELAJARAN TEKNIK DASAR LISTRIK DAN ELEKTRONIKA - Febby Dwi Al Indra; Ika Parma Dewi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Basic Electrical and Electronics Engineering (DLE) is a subject that has theory and practice, students are required to play an active role in learning so that they understand the material being taught, these subjects are the basis for students to understand and understand electronic components. SMK Negeri 1 Padang is one of the schools that has taken advantage of technological developments, such as the use of computers and Liquid Crystal Display or LCD projectors in the learning process. The purpose of this study is to improve student learning outcomes by using interactive media in the teaching and learning process. This research produces interactive learning media for basic electrical and electronic techniques. The media was then tested through computers and several people who understood interactive learning media and were revised based on suggestions and input from examiners, then tested their feasibility for use in the teaching and learning process. From the results of the trial it can be concluded that the media designed can run as it should and is suitable for use in the teaching and learning process at SMK Negeri 1 Padang.Keywords : Interactive Media, Adobe Flash CS6, Basic Electricity and Electronics.